2022
DOI: 10.1037/apl0000901
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to update and expand training motivation theory? A meta-analytic review of training motivation research in the 21st century.

Abstract: theory based on meta-analysis and model testing has served as the foundation for our understanding of training motivation. However, the applicability of the theory today may be limited for several reasons. There has been significant growth in training motivation research since Colquitt et al. (Journal of Applied Psychology, 2000, 85, p. 678) proposed and tested their theory. Also, advances in meta-analysis and model testing allow for a more complete and rigorous test of the theory than was previously possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 153 publications
2
32
0
Order By: Relevance
“…In this sense, our results also confirm the utility of the Social Learning Theory [13,14], which is one of the most used theories to guide programs and training that develop social skills. Moreover, a participatory approach was implemented (e.g., role-playing techniques, group discussions), which facilitated the active involvement of participants in the planning and development of the training and therefore may have improved their motivation and intention to apply the training content to their daily job [39]. Such a participatory approach has been successfully implemented to promote more sustainable communities and quality of life [40,41] and deserves further attention when implementing training programs aimed at promoting sustainable behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our results also confirm the utility of the Social Learning Theory [13,14], which is one of the most used theories to guide programs and training that develop social skills. Moreover, a participatory approach was implemented (e.g., role-playing techniques, group discussions), which facilitated the active involvement of participants in the planning and development of the training and therefore may have improved their motivation and intention to apply the training content to their daily job [39]. Such a participatory approach has been successfully implemented to promote more sustainable communities and quality of life [40,41] and deserves further attention when implementing training programs aimed at promoting sustainable behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Yet there is paucity of work with indepth inquiry into the differences in learning attributes between Gen X and Millennials which can be used to choose appropriate teaching pedagogies that would engage each generation with learning. This study aims to fill this gap and we hypothesise that: H1: Gen X and Millennials differ in their learning attributes It is well established that there is significant correlation between training motivation and succeeding affect (Chung et al, 2021;Tannenbaum, Mathieu, Salas & Cannon-Bowers, 1991;Mathieu, Tannenbaum & Salas, 1992), learning (Noe 1986;Baldwin et al, 1991;Mathieu, Tannenbaum & Salas, 1992;Clark et al, 1993) and performance (Lee, 2019;Hicks & Klimoski, 1987). However, the interaction between these learning differs for Millennials and Gen X has not received adequate attention.…”
Section: Hypothesismentioning
confidence: 96%
“…Concerning the theory of training motivation, Chung et al [12] developed a model based on a meta-analysis in which they included variables that had not been considered in the work of Colquitt et al [13], as shown in Table 1. From Table 1, there are five areas that benefit from the theoretical model which is shown in Table 2.…”
Section: Motivation Associated With Sports Environmentsmentioning
confidence: 99%
“…Thus, since the end of the previous century, studies focused on motivation to learn (as is the case with the previous model) have been used as a basis in the theory of training motivation [12].…”
Section: Motivation Associated With Sports Environmentsmentioning
confidence: 99%
See 1 more Smart Citation